The relationship between helicobacter pylori infection and hyperemesis Gravidarum in first trimester of pregnancy - Alireza Rezaee; Misaghallah Tavakoli; Zahra Mostafavian; Parisa Zarif Najafi (Mashhad University of Medical Sciences, 2022)
Introduction: Frequent nausea and vomiting in the first trimester of pregnancy is seen in more than half of pregnancies. Severe nausea and vomiting in pregnancy, called hyperemesis gravidarum, sometimes persists until the pregnancy termination. The present study was performed aimed to determine the relationship between Helicobacter pylori infection and hyperemesis gravidarum in pregnant women.Methods: In this case-control study which was performed in 2017-2019, 83 pregnant women with Hyperemesis gravidarum as cases and 83 pregnant women with no symptom of sever vomiting as controls entered the study. The data were collected through a questionnaire containing demographic information of mothers as well as questions about the frequency of retching, vomiting and the feeling of sick to their stomach. Serum levels of anti-Helicobacter pylori immunoglobulin G were measured in participants. Data were analyzed by SPSS (version 20) and chi-square, T-test, and logistic regression. P<0.05 was considered statistically significant.Results: The frequency of Helicobacter pylori seroposivity in case group and control group were 33.7%, 18.1%, respectively, this difference was statistically significant (P=0.021). Logistic regression showed that among the variables of age, parity, gravidity, BMI, gestational age, and Helicobacter pylori infection, only Helicobacter pylori infection was found as a risk factor for hyperemesis gravidarum (p=0.017) (OR= 2.524, CI 95%= 1.180-5.400).Conclusion: In this study, there was a significant difference between Helicobacter pylori and Hyperemesis gravidarum. Since there is no specific therapy for Hyperemesis gravidarum, it can be one of the goals of future studies.